Functional Characterization of Paralogous Gonadotropin-Releasing Hormone-Type and Corazonin-Type Neuropeptides in an Echinoderm - Tian, Shi; Egertová, Michaela; Elphick, Maurice R. (Frontiers in Endocrinology, 2017)
Homologs of the vertebrate neuropeptide gonadotropin-releasing hormone (GnRH) have been identified in invertebrates, including the insect neuropeptide corazonin (CRZ). Recently, we reported the discovery of GnRH-type and CRZ-type signaling systems in an echinoderm, the starfish Asterias rubens, demonstrating that the evolutionary origin of paralogous GnRH-type and CRZ-type neuropeptides can be traced back to the common ancestor of protostomes and deuterostomes. Here we have investigated the physiological roles of the GnRH-type (ArGnRH) and the CRZ-type (ArCRZ) neuropeptides in A. rubens, using mRNA in situ hybridization, immunohistochemistry and in vitro pharmacology. ArGnRH precursor-expressing cells and ArGnRH-immunoreactive cells and/or processes are present in the radial nerve cords, circumoral nerve ring, digestive system (e.g. cardiac stomach and pyloric stomach) and body wall-associated muscle (apical muscle) and appendages (tube feet, terminal tentacle). The general distribution of ArCRZ precursor-expressing cells is similar to that of the ArGnRH precursor, but with specific local differences. For example, cells expressing the ArGnRH precursor are present in both the ectoneural and hyponeural regions of the radial nerve cords and circumoral nerve ring, whereas cells expressing the ArCRZ precursor were only observed in the ectoneural region. In vitro pharmacological experiments revealed that both ArGnRH and ArCRZ cause contraction of cardiac stomach, apical muscle and tube foot preparations. However, ArGnRH was more potent/effective than ArCRZ as a contractant of cardiac stomach, whereas ArCRZ was more potent/effective than ArGnRH as a contractant of apical muscle. These data demonstrate that both ArGnRH and ArCRZ are myoexcitatory neuropeptides in starfish, but differences in their expression patterns and pharmacological activities are indicative of distinct physiological roles. This is the first study to investigate the physiological roles of both GnRH-type and CRZ-type neuropeptides in a deuterostome, providing new insights into the evolution and comparative physiology of these paralogous neuropeptide signaling systems in the Bilateria.